O impacto do nível educacional e da localização como fatores de diferenciação na renda do trabalhador formal no Brasil entre 1999 A 2006 - Carvalho, Francelena Saraiva Marques (2010)
This dissertation examines the impact of the educational cause and location of the pay differentials between workers in Brazil during the period 1999 to 2006, with the base category to the Northeast. To achieve this goal, we used data on employment relationship, level of education of workers and the average wage received by them, where such data were obtained from the Annual Social Information (RAIS). The methodology focuses on descriptive statistics and an econometric model for panel data. To capture possible wage differentials between workers in Brazilian regions, we used regional dummies. The results indicate that in general, for some sectors of the economy, there is a degree of spatial and temporal differentiation of the average wage of formal workers.